Neue Methode zur Bestimmung und Beschreibung der taktfrequenten Stromsteigungen in Drehstromsynchronmaschinen - Liske, Andreas (KIT Scientific Publishing, 2022)
Knowledge of the cycle-frequency changes in the machine currents is of great advantage for many methods of controlling modern, highly utilized electrical machines. But how can these changes in machine currents be reliably measured during operation? Is the very short time of the individual switching states sufficient? And how can the changes in the currents be described mathematically and interpreted physically? This work provides an answer to these questions.